Tinjauan Terhadap Aturan Hukum Penggantian Status Jenis Kelamin di Kawasan Asia Tenggara (Studi Kasus Negara Indonesia dan Malaysia) - Ikhsan, Varian; Nugraheni, Anjar Sri Ciptorukmi (Peneliti.net, 2024)
This article aims to analyze the legal regulations regarding gender identity change in Southeast Asian countries. The legal analysis focuses on general provisions/legality regarding gender identity change, rules regarding the sequence of procedures for gender identity change, and regulations aimed at providing supervision, guidance, and ensuring the absence of discriminatory treatment towards transgender groups, with Indonesia and Malaysia being the study variables in this article. The research type conducted here is doctrinal research of a descriptive nature, utilizing a legal approach, case analysis, and a comparative approach. This research utilizes primary legal materials, including legislative regulations and court judgments related to gender identity change, as well as secondary legal materials such as research findings discussing legal regulations regarding gender identity change (both domestically and internationally published). The data collection method for legal materials involves a literature review, while the legal material analysis employs deductive syllogism as the method. The research findings indicate that Indonesia does not have clear legal provisions regulating the legality of transgender individuals, whereas Malaysia, within its two legal systems, firmly rejects legalizing the existence of transgender individuals. Concerning the procedural process, citizens of Indonesia and Malaysia desiring a change in their gender status are required to obtain prior approval from the court. Finally, both Indonesia and Malaysia lack legal instruments to provide protection and prevent discriminatory treatment against transgender groups.